Counselling for Asperger couples - Thompson, Barrie (Jessica Kingsley, 2008)
Annotation Asperger Counselling for Couples is the first book to provide a model for counselling couples where one partner or a child has Asperger Syndrome. The book provides details of the different stages of the model and includes anecdotal evidence from clients who have used it. The author explains the importance of initial separate counselling, and describes the co-counselling process using case studies to demonstrate useful strategies. The book offers valuable advice on improving communication and cooperation, and includes photocopiable activity sheets. Based on considerable experience and research, this book will be invaluable for counsellors treating couples where one partner has Asperger Syndrome.